Infection prevention with natural protein-based coating on the surface of Foley catheters: a randomised controlled clinical trial. (October 2016) - Zhao, Peng; Chen, Qijing; Lin, Chao; Lin, Zhaofen; Chang, Liang; Shao, Xiaoping; Li, Yueming; Zhang, Jiangong; Fan, Zhongpeng; Wen, Xuejun
Abstract: Background: Health-care-associated infections characterised by antibiotic drug resistance are a global medical challenge that claims billions of dollars of health-care expenditure. Bacterial adhesion and subsequent formation of biofilms on catheters and tubes are the primary mechanisms through which these infections are initiated and propagated. We tested the efficacy and safety for clinical treatment of a coating based on natural protein, in which immunogenicity was eliminated through physical plasticising, applied to the surfaces of medical devices to inhibit bacterial adhesion. Methods: We did a randomised clinical trial in two hospitals in China (Shanghai Changzheng Hospital and 254th Hospital of Chinese People's Liberation Army in Tianjin), in men and women without urinary tract infection, aged 18–75 years, who required urethral catheterisation. Patients who were pregnant, perinatal, or allergic to silicon rubber or protein, or who had any other diseases (eg, cystitis, stress incontinence, mental or neurological disorders, or severe heart, liver, lung, or kidney failures) not suitable for the study were excluded. All patients who provided written informed consent were enrolled and assigned to groups using a random envelope. Patients received Foley catheters with (test group) and without (controls) the coating. Primary outcomes were differences between groups in bacterial colony count and amount of mineral deposition, analysed by Fisher exact test, and leucocytes and occult blood in urine, analysed by χ 2 /Fisher exact test. To reduce uncertainty owing to participants' use of antibiotics, we designed two-section sampling projects to assess catheter sections in the bladder and out of the urinary meatus. Chinese Food and Drug Administration (Jiangsu province) regulatory code 2014-ZC-440; hospital ethics committee coding EC-Device-2014-18 and EC-Device-2015-08. Findings: Between July, 2014, and November, 2015, we randomly assigned 67 patients to the test group and 65 to the control group. Urinary mineral deposition occurred in five (8%) patients in test group and 22 (34%) in control group (χ 2 =14·11, OR 0·16, 95% CI 0·06–0·45, p=0·0002). Bacterial colonisation was present in catheter sections out of the urinary meatus for 18 test patients (27%) and 44 (68%) controls (OR 0·16, 95% CI 0·08–0·37, p<0·0001), and in bladder for 27 (40%) test patients and 44 (68%) controls (0·32, 0·16–0·66, p<0·0001). There were no significant differences between the groups in leucocytes and occult blood in urine before, during, or after catheterisation (p>0·05). No adverse events occurred in either group. Interpretation: The coating can effectively and safely inhibit biofilm formation on catheter surface and reduce urinary mineral deposition. Funding: National Basic Research Program of China (2014CB964603, 2012CB966300), National Natural Science Foundation of China (81271958), Center for Innovation Technology (MF13-005-LS), William H Goodwin Endowment.